2009
DOI: 10.1148/radiol.2521080696
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Digital Mammography in a Population-based Breast Cancer Screening Program: Effect of Screening Round on Recall Rate and Cancer Detection

Abstract: Digital mammography may reduce the adverse effects of screening programs if this technique is confirmed to have the same diagnostic accuracy as screen-film mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…29,81,82 Breast density is therefore also explanatory of the greater risk for FP results in pre-menopausal females than in post-menopausal females. 36,83 Inherent limitations of conventional mammography Poor discrimination between malignant and benign pathologies can be linked to limitations inherent to the method by which a mammogram is acquired. The two-dimensional (2D) projection of an X-ray beam through a three-dimensional volume of soft tissue results in the unavoidable superimposition of various structures upon an intricate network of the glandular tissue.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…29,81,82 Breast density is therefore also explanatory of the greater risk for FP results in pre-menopausal females than in post-menopausal females. 36,83 Inherent limitations of conventional mammography Poor discrimination between malignant and benign pathologies can be linked to limitations inherent to the method by which a mammogram is acquired. The two-dimensional (2D) projection of an X-ray beam through a three-dimensional volume of soft tissue results in the unavoidable superimposition of various structures upon an intricate network of the glandular tissue.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Authors of previous populationbased studies comparing the accuracy of SFM and FFDM have shown conflicting results, particularly with respect to age-specific performance (4)(5)(6)(7). The reported recall rates for FFDM compared with those for SFM have varied widely (3,5).…”
Section: Breast Imaging: Transition From Screen-film To Full-field DImentioning
confidence: 99%
“…M ammography is the current standard for breast cancer screening because of its impressive advantages for detection performance, imaging time, and cost-effectiveness (1)(2)(3)(4)(5). However, radiologists also widely recognize its limitations, especially for dense breasts (6)(7)(8).…”
Section: Methodsmentioning
confidence: 99%